Making transparency work - Mueller, Christoph E. (Central European Public Administration Review, 2018)
Freedom of information acts (FOIA) aim to improve the public's opportunities to access official information from public authorities and hence to increase the level of transparency. Thus, it is important to know whether and to what degree the effects intended by establishing FOIAs are achieved and how their implementation could be improved. Hence, this article presents the evaluation of the Hamburg Transparency Law (HmbTG) - Germany's first FOIA that binds authorities to disclose government information proactively. The purpose of the paper is to provide a valuable example of how evaluating FOIA might produce useful information for policymakers and public authorities. The analysis results, based on a mixed set of methods (i.e. standardised surveys, statistical secondary data, qualitative expert interviews, and criteria-driven document analysis), lead to the conclusion that the HmbTG was very effective in providing the direct access. On the other hand, it was found that strategies for implementing the law varied considerably between authorities, yet proactive disclosure was overall implemented effectively. Moreover, this law shows some weaknesses to be improved in the future. Besides providing practitioners with valuable insights into how a transparency law may be implemented, the evaluation of the HmbTG also provides researchers with ideas how FOIA evaluation might be conducted comprehensively.
Keywords: dostop do informacij; FOIA; HmbTG; informacije; preglednost; proaktivnost; vrednotenje